تحديات المراجعة الخارجية في ظل توجه النظام المحاسبي المالي نحو محاسبة القيمة العادلة ــــــ دراسة تحليلية لآراء عينة من الأكاديميين والمهنيين في الجزائر ـــــ - مناصرية, جوهر (جامعة الوادي - University of Eloued, 2023)
يهدف هذا البحث إلى التعرف على أهم التحديات والصعوبات التي يواجهها المراجع الخارجي عند قيامه بمراجعة حسابات المؤسسة في ظل تبني النظام المحاسبي المالي للقيمة العادلة كنموذج من نماذج القياس المحاسبي؛ وذلك من خلال الاستعانة بآراء مجموعة من المهتمين بالمحاسبة والمراجعة من أكاديميين ومهنيين. وتوصلنا إلى أن تبني النظام المحاسبي المالي لنموذج القيمة العادلة كأحد أساليب التقييم المحاسبي في ظل غياب سوق مالي نشط في الجزائر، وتعدد النماذج والأساليب المستخدمة لقياسها؛ جعل المراجع الخارجي يواجه العديد من التحديات والصعوبات، لأن البيئة الاقتصادية والقانونية في الجزائر غير مناسبة لتطبيق نموذج القيمة العادلة This research aims to identify the most important challenges and difficulties faced by the external auditor when auditing the accounts of the institution in light of the adoption of the financial accounting system of fair value as a model of accounting measurement.This is done by seeking the opinions of a group of academics and professionals interested in accounting and auditing. We concluded that the financial accounting system adopted the fair value model as one of the accounting evaluation methods in the absence of an active financial market in Algeria, and the multiplicity of models and methods used to measure it; Making the external auditor face many challenges and difficulties, because the economic and legal environment in Algeria is not suitable for applying the fair value model.
The challenges of external auditing in light of the financial accounting system's orientation towards fair value accounting -an analytical study of the opinions of a sample of academics and professionals in Algeria -
مقال
Keywords: القيمة العادلة ; النظام المحاسبي المالي ; المراجعة الخارجية ; تحديات المراجعة الخارجية: fair value, financial accounting system, external audit,external audit challenges.